Agribusiness System and Maize Agriculture Development Strategy in Palolo District Sigi Regency - Sofya A. Rasyid; Made Antara; Alam Anshary; Effendy; Hadayani (Jurnal Penelitian Pendidikan IPA, 2024)
Maize productivity in Palolo District only reaches 4.8 tons/ha, far below the national average.  Suboptimal cultivation techniques, limited access to superior seeds, and the use of fertilizers and pesticides that are not in accordance with the recommendations. Farmers' limited knowledge of modern agricultural practices and lack of access to technology and training also affect production yields. A synergistic agribusiness system ensures integration between the upstream and downstream sectors. The purpose of this study is to analyze the success of the maize agribusiness system and formulate a strategy for the development of the maize agribusiness system. The sampling technique is purposive sampling. The analysis method uses agribusiness index, SWOT analysis and AHP. As a result of the calculation of the agribusiness system index, the value obtained is 11.4 from the maximum value of 17.4 or 65.5%.  It shows that the maize agribusiness system is running well, in a good value interval (8.71-17.40). As a result of the SWOT and AHP analysis, there are four main strategies for the development of maize agribusiness: Improving farmers' skills through training and mentoring the latest agricultural technology (weight 0.225), optimizing land use and maximizing production (weight 0.219), increasing maize productivity with active extension and technological innovation (weight 0.137), increasing productivity and availability of facilities through the adoption of sustainable agricultural practices and environmentally friendly technology (weight 0.106).